Photobiomodulation mechanisms: duration of action in the human prefrontal cortex - O’Connor, Patrick; Lime, Turner; Barrett, Douglas W.; Gonzalez-Lima, F. (Frontiers in Behavioral Neuroscience, 2025)
IntroductionTranscranial infrared laser stimulation (TILS) is a form of photobiomodulation (PBM) using a wavelength of 1064 nm shown to enhance metabolic and hemodynamic activity in the human prefrontal cortex (PFC). Prior studies have shown that when applied to the PFC in the right hemisphere, TILS improves PFC-based memory and learning and sustains attention and mood in healthy adults. However, the temporal duration of PBM mechanisms following a single administration remains poorly understood in humans. The objective of this study was to evaluate the duration of functional connectivity effects of a single administration of TILS to the right anterior PFC during both resting-state and memory-activated conditions over a 5-day period.MethodsHemodynamics-derived functional connectivity of the PFC in 12 healthy adults was measured using a 48-channel functional near-infrared spectroscopy (fNIRS) during 5-min resting-state and 2-back memory task activation phases, collected at six time points over a 5-day span. A sham-controlled, within-subject crossover design was employed: all participants received both sham and active TILS in counterbalanced order, with a 4-week washout period between sessions.ResultsRelative to sham, a single administration of TILS significantly modulated PFC functional connectivity during cognitively demanding memory tasks across the 5-day assessment period. No significant effects were observed during resting-state measurements. No adverse effects were reported.DiscussionThese findings suggest that a single administration of TILS can induce functional neuroplasticity in the PFC that persists for several days. The results advance understanding of PBM mechanisms and may inform future interventions aimed at promoting longer-lasting neurocognitive benefits.